1991
DOI: 10.1177/0013161x91027002005
|View full text |Cite
|
Sign up to set email alerts
|

Building an Ethical School: A Theory for Practice in Educational Leadership

Abstract: During ordinary times, which are never ordinary, but especially during a period of school restructuring, educational administrators need to consider their responsibility to promote an ethical environment in their schools. This article develops three foundational ethical themes-critique, justice, and caring-as the pillars on which to build such a school

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
257
0
24

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(282 citation statements)
references
References 8 publications
1
257
0
24
Order By: Relevance
“…Cuestiones como la herencia cultural (lenguaje, literatura, arte) y el peso del patrimonio histórico determinan en gran medida el enfoque sobre lo que signiica ética del liderazgo educativo y qué preguntas habría que plantear sobre esta cuestión desde nuestra perspectiva y nuestro contexto. El liderazgo educativo propone una práctica de gestión educativa basada en el respeto por la persona en todos sus roles (Starratt, 1991;Langlois, 2005;Membiela, 2007) desde la relexión y la consideración del impacto que unas decisiones tomadas a nivel organizativo y educativo tiene en la vida humana. Tomar consciencia de estos efectos es la base de una experiencia compartida que genere un clima de respeto y consideración mutuos dentro de comunidades y/o instituciones educativas, es decir, el clima característico de las llamadas organizaciones saludables, opuestas al característico de las organizaciones tóxicas.…”
Section: La Necesaria Reorientación Del Liderazgo Educativo Hacia Un unclassified
See 1 more Smart Citation
“…Cuestiones como la herencia cultural (lenguaje, literatura, arte) y el peso del patrimonio histórico determinan en gran medida el enfoque sobre lo que signiica ética del liderazgo educativo y qué preguntas habría que plantear sobre esta cuestión desde nuestra perspectiva y nuestro contexto. El liderazgo educativo propone una práctica de gestión educativa basada en el respeto por la persona en todos sus roles (Starratt, 1991;Langlois, 2005;Membiela, 2007) desde la relexión y la consideración del impacto que unas decisiones tomadas a nivel organizativo y educativo tiene en la vida humana. Tomar consciencia de estos efectos es la base de una experiencia compartida que genere un clima de respeto y consideración mutuos dentro de comunidades y/o instituciones educativas, es decir, el clima característico de las llamadas organizaciones saludables, opuestas al característico de las organizaciones tóxicas.…”
Section: La Necesaria Reorientación Del Liderazgo Educativo Hacia Un unclassified
“…Desde la publicación de Tras la virtud, de MacIntyre (1997), pero también a principios de los años noventa con los trabajos de Starratt (1991), Hodgkinson (1991), Sergiovanni (1992) y Johnson (2001), la ética de las virtudes ha experimentado un gran desarrollo. La reivindicación de una ética neoaristotélica basada en las virtudes ha inspirado diversas éticas aplicadas, entre ellas la ética de la educación.…”
Section: Liderazgo Educativo Basado En Virtudesunclassified
“…For example, Burns (1978) wrote that transformative leaders need to act in a moral capacity by elevating their followers and, in turn, being elevated by them. Starratt (1991) suggested that leaders base their practices on the ethics of care, justice, and critique. McCarthy (2005) spoke of the "practiced reflexivity" of leaders who consciously take responsibility for their actions and realize that these have a profound impact on the school community; the work of Mezirow (1997), Dirkx (2001), and Cranton (2002) follows this line of emphasis.…”
Section: International Journal Of Educationmentioning
confidence: 99%
“…The framework is situated in a larger "multiple paradigm" ethical landscape of justice, care, and critique (Starratt 1991(Starratt , 1994. A brief consideration of these theoretical standpoints serves as a backdrop for ethical and moral leadership.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…What is known currently about the topics of values, ethics, and moral leadership in the field of educational leadership pertains to how practicing educational leaders approach, or should approach, decision making and their consequent actions along various ethical frameworks, that is, justice, care, critique, community, administrative virtue, and other moral vantage points (Schussler and Collins 2006;Starratt 1991).…”
mentioning
confidence: 99%